2021
DOI: 10.1590/1980-220x-reeusp-2020-0547
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nursing workload in a Pediatric Intensive Care Unit estimated by three instruments

Abstract: Objective: To compare the nursing workload using the Nursing Activities Score (NAS), Therapeutic Intervention Scoring System-28 (TISS-28) and Nine Equivalents of Nursing Manpower Use Score (NEMS) instruments in children admitted to a Pediatric Intensive Care Unit in a university hospital. Method: A prospective cohort study performed in a Pediatric Intensive Care Unit, with a sample formed of all children hospitalized during the study period. Nursing workload was evaluated using the TISS-28, NEMS and NAS instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…1 Not surprisingly, our study demonstrated variation in nursing workload between and within reason for admission, and estimated lower nursing workload for patients who do not require critical care-specific interventions, but future studies using a more detailed scoring system may be helpful in defining health care provider skill sets required to care for these children. 26…”
Section: Discussionmentioning
confidence: 99%
“…1 Not surprisingly, our study demonstrated variation in nursing workload between and within reason for admission, and estimated lower nursing workload for patients who do not require critical care-specific interventions, but future studies using a more detailed scoring system may be helpful in defining health care provider skill sets required to care for these children. 26…”
Section: Discussionmentioning
confidence: 99%
“…The reliance on NEMS as the primary workload measurement tool may not capture the full complexity of nursing activities, and better scores may be available, such as the Nursing Activity Score. 32,33 We did not aim to compare scoring systems or have a full capture of activity, rather we focused on the tool allowing fast and routine workload evaluation. The weak correlation between objective workload measures and perceived workload suggests unexplored factors.…”
Section: Limitationsmentioning
confidence: 99%
“…The test results were then converted into hours (according to the guidelines for each tool). For TISS-28 the average nurse workload for the analyzed hospitalization days (expressed in minutes) was multiplied by 3, and the result was divided by 60'according to the methodology of the tool [29,30]. Calculations using TISS-28 omit the conversion of the average result into minutes (multiplied by 10.6') because the collected data was expressed and analyzed in a minute record.…”
Section: Instrumentsmentioning
confidence: 99%
“…For the NEMS tool, the average (expressed in points) of day and night duty was multiplied by 10.6'. The result in minutes was multiplied by 3, followed by the result being divided by 60' [14,[29][30].…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation